1997
DOI: 10.4315/0362-028x-60.11.1400
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Hazards and Emerging Issues Associated with Produce A Preliminary Report to the National Advisory Committee on Microbiologic Criteria for Foods

Abstract: In the past two decades, the consumption of fresh fruits and vegetables in the United States has increased, and the geographic sources and distribution of fresh produce have expanded greatly. Concomitantly, public health officials have documented an increase in the number of reported produce-associated foodborne disease outbreaks in the United States. The Centers for Disease Control and Prevention (CDC) reports that the number of these outbreaks doubled between 1973 and 1987, and 1988 and 1991, and that the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
140
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(148 citation statements)
references
References 0 publications
0
140
0
3
Order By: Relevance
“…On the other hand, the fate of E. coli populations under complex natural conditions is often not accurately predictable . Although the conditions for survival of E. coli in soil, manure and water are considered to be less favourable than in the intestinal system (Tauxe et al, 1997), the organism has been observed to survive for days (at physiological (430 1C) temperature, aerobic and under nutrient-limiting conditions) to almost a year in the former habitats (Kudva et al, 1998;Fukushima et al, 1999;Jiang et al, 2002).…”
Section: Factors Affecting E Coli Fate In Open Environmentsmentioning
confidence: 99%
“…On the other hand, the fate of E. coli populations under complex natural conditions is often not accurately predictable . Although the conditions for survival of E. coli in soil, manure and water are considered to be less favourable than in the intestinal system (Tauxe et al, 1997), the organism has been observed to survive for days (at physiological (430 1C) temperature, aerobic and under nutrient-limiting conditions) to almost a year in the former habitats (Kudva et al, 1998;Fukushima et al, 1999;Jiang et al, 2002).…”
Section: Factors Affecting E Coli Fate In Open Environmentsmentioning
confidence: 99%
“…Já foram incriminados em surtos, dentre outros alimentos, leite cru, carne bovina mal cozida e outros produtos à base de carne (rosbifes, hambúrgueres e salsichas tipo "hot-dog"), frutas e vegetais (alface, melão, suco de maçã e diversos tipos de saladas) e maionese industrializada [3,6,15]. No geral, pode-se dizer que a carne bovina é uma das principais fontes potenciais de E.coli O157:H7, uma vez que o trato gastrointestinal de bovinos é o reservatório desses microrganismos [7].…”
Section: Ocorrência De Escherichia Coli O157:h7 Em Produtos Cárneos Eunclassified
“…However, further efforts are needed to sustain these declines, to reduce pathogens in food animal reservoirs, and to prevent the contamination of produce. Among the outbreaks associated with fresh produce consumption and for which the etiology has been determined, Salmonella enterica serovar Enteritidis accounted for the largest number of outbreaks, cases, and deaths, followed by Escherichia coli O157: H7, which was frequently found during multistate outbreaks (42).…”
mentioning
confidence: 99%